Correlation Studies among Morpho-Physiological Characters in Eight Sunflower Parents and Their Sixteen F1 Hybrids - Muhammad Saeed, Shah Masaud Khan, Bashir Ahmad, Sher Asalm Khan, Habib Ahmad, Ayub Khan (Recent Research in Science and Technology, 2009)
Eight sunflower parents and their sixteen F1 hybrids were evaluated at Agricultural Research Institute Tarnab, Peshawar during autumn 2006-07 to estimate correlation among different Morpho-physiological characters. A randomized complete block design with three replicates was used. The correlation study has indicated that days to maturity was positively linked with days to first flowering, days to 100 percent flowering, internodes length and stem girth. Plant height was positively correlated with stem girth, number of leaves, days to first flowering, days to 100 percent flowering and internodes length. As revealed from results obtained that to evolve sunflower hybrid with early maturity, short stature, focus should be given to select parents having maximum stem girth, number of leaves, leaf area and minimum days to maturity and internodes length.